Some Backward in Time Results for Thermoelastic Dipolar Structures - Marin, Marin I.; Abbas, Ibrahim A.; Vlase, Sorin; Craciun, Eduard-Marius (Frontiers in Physics, 2020)
In our study we define the linear problem of backward in time for a thermoelastic body having a dipolar structure. In our first main result we prove the uniqueness of solution for this problem. Then, we approach the question of the impossibility to locate in time for the solution of this problem.